Rational Antibiotic Therapy - a Condition of the Efficacy of Acute Otitis Media Treatment in Young Children - Ye.I. Yulish; O.Ye. Chernyshova; B.I. Krivuschev; Ye.V. Glinskaya (Zaslavsky O.Yu., 2013)
The paper presents the current approaches to the indications and carrying out rational antibiotic treatment of acute otitis media in children.